American journal of physical anthropology : official publication of the American Association of Physical Anthropologists - American Association of Physical Anthropologists; Johnston, Francis E. (Spruce, Philadelphia : Wistar Institute Press, 1978)
"The American Journal of Physical Anthropology is designed for the prompt publication of original and significant articles on human evolution and variation, including primate morphology, physiology, genetics, adaptation, growth, development, and behavior present and past."
Morphoclinical variation in the anthropod shoulder. Corruccini, Robert S. and Ciochon, Russel L.
Includes bibliographical references and index.
in English.
Keywords: Physical anthropology -- Periodicals. Societies. Serials; Antiquities, Prehistoric; Prehistoric peoples